Unconditional Acceptance in Crisis Work Based on the Lived Experience of Malaysian Counselors - Nur Husna Mohd Hafiz; Muhammed Fauzi Othman; Mohd Zaliridzal Zakaria; Wan Mohd Fazrul Azdi Wan Razali; Nurhafizah Mohd. Sukor; Marina Munira Abdul Mutalib (Global Academic Excellence, 2024)
Indexed by MYCITE